2021
DOI: 10.1021/acsaem.1c02892
|View full text |Cite
|
Sign up to set email alerts
|

Borohydride Substitution Effects of Li6PS5Cl Solid Electrolyte

Abstract: We report an electrochemically stable borohydride (BH 4 − )-substituted Liargyrodite solid electrolyte prepared by a mechanical ball-milling method. The crystal structure of BH 4 − -substituted argyrodite remains unchanged with x < 0.3 (Li 6 PS 5 Cl 1−x (BH 4 ) x ), whereas a complex phase (Li 2 S-P 2 S 5 -LiCl-LiBH 4 ) was obtained with x > 0.3. The highest ionic conductivity of 0.12 mS cm −1 at 25 °C was observed with x = 0.1 in Li 6 PS 5 Cl 1−x (BH 4 ) x , whereas there was virtually no change in the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The observed peak positions coincided with the cubic crystal structure with the F 4̅3 m space group. This confirmed the successful formation of Li-argyrodite type solid electrolyte. In addition, Li 3 PO 4 impurity peaks were observed at 2θ = 22.0°, 22.9°, 24.5°; Li 2 S and LiCl impurity peaks were observed at 26.8° and 49.9°, respectively . Usually, impurity peaks of Li 3 PO 4 , Li 2 S, and LiCl are observed during the preparation of argyrodite solid electrolyte by solution synthesis.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The observed peak positions coincided with the cubic crystal structure with the F 4̅3 m space group. This confirmed the successful formation of Li-argyrodite type solid electrolyte. In addition, Li 3 PO 4 impurity peaks were observed at 2θ = 22.0°, 22.9°, 24.5°; Li 2 S and LiCl impurity peaks were observed at 26.8° and 49.9°, respectively . Usually, impurity peaks of Li 3 PO 4 , Li 2 S, and LiCl are observed during the preparation of argyrodite solid electrolyte by solution synthesis.…”
Section: Resultssupporting
confidence: 54%
“…Thus, the solid electrolyte prepared by normal drying showed high conductivity (4.6 mS cm −1 ) at room temperature and was comparable to the ball-mill method. 11,19 In the case of vacuum drying, we observed impurity peaks in the XRD pattern, and no semicircles were observed in the Nyquist plot, indicating a complete drying process (Figures S1 and S2). Thus, vacuum drying successfully removed pyridine solvent and enhanced ionic conductivity.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…[ 4 ] Furthermore, this conductivity value is much higher than those reported in previous studies on borohydride argyrodite materials. [ 7 , 8 , 9 , 17 ] This result can be attributed to the thiophosphate local structure of the prepared materials, which is favorable for Li‐ion conduction. The local structure was closely examined as described later.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, Cl or I in the argyrodite crystal was partially or fully replaced with borohydride ions. [ 9 ] The borohydride‐substituted materials exhibited a higher stability with Li metal and enhanced ionic conductivities than did Li 6 PS 5 X (X = Cl and I). However, the ionic conductivity was still low, and the effect of the local structure of the thiophosphate on the ionic conductivity remains hitherto underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…13,16 Wang et al reported on BH 4 − -substituted Li 6 PS 5 Cl electrolytes with a low conductivity of 0.12 mS cm −1 at room temperature. 12 They heated the sample to 550 °C, and it is likely that BH 4 − did not substitute for X − but decomposed. Furthermore, they ball milled all the precursors together.…”
Section: Introductionmentioning
confidence: 99%